2011
DOI: 10.1111/j.1467-9752.2011.00799.x
|View full text |Cite
|
Sign up to set email alerts
|

The Provocation of an Epistemological Shift in Teacher Education through Philosophy with Children

Abstract: Experience indicates that the questioning and democratic nature of the community of enquiry can be demanding and unsettling for teachers, presenting unaccustomed challenges and moral dilemmas. This paper argues that such significant episodes in the practice of Philosophical with Children (PwC) offer rich opportunities for wider critical reflection on epistemological and pedagogical questions for teacher education and continuing professional development. We illustrate the nature of this ongoing work through not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 29 publications
(31 reference statements)
0
24
0
2
Order By: Relevance
“…For example, after using PCoE in professional development activities for teachers, Haynes and Murris (2011) found that it provided a transformative critical space for exploring epistemological and pedagogical questions about experienced teachers' practice. Similarly, Scholl et al found that it was a catalyst for indepth reflection because of the way it challenged and extended teachers' pedagogical orientations towards more learner-centred and enquiry-based approaches (Scholl, 2011).…”
Section: The Affordances Of a Philosophical Community Of Enquiry (Pcoe)mentioning
confidence: 99%
“…For example, after using PCoE in professional development activities for teachers, Haynes and Murris (2011) found that it provided a transformative critical space for exploring epistemological and pedagogical questions about experienced teachers' practice. Similarly, Scholl et al found that it was a catalyst for indepth reflection because of the way it challenged and extended teachers' pedagogical orientations towards more learner-centred and enquiry-based approaches (Scholl, 2011).…”
Section: The Affordances Of a Philosophical Community Of Enquiry (Pcoe)mentioning
confidence: 99%
“…Teacher self-identity as epistemic authority may sometimes constitute a serious barrier to hearing children's voices, even when their ideas are deliberately solicited in the classroom (Haynes & Murris 2011). Children consequently require opportunities to actively engage in democratic decision-making processes-first within the school and then within their local communities-before they can learn to abide by subsequent decisions in society as they grow up (Lansdown 2001).…”
Section: Enabling Identity Journal Of Philosophy In Schools 3(1)mentioning
confidence: 99%
“…They explain that interrupting with questions destabilizes pupils' representations and, in so doing, leads to problematizing ideas and to more sustained argumentation. In short, to these authors, interruption by questioning leads to a process of critical inquiry that results in a more complex resolution of the problem posed or a more refined representation of the concept being discussed (Barth, 2008;Berland & McNeill, 2010;Golding, 2009;Haynes & Murris, 2011;Karabulut, 2012;Martin & Hand, 2009). …”
Section: Impact Of Questions (Closed and Open) On Pupils' Cognitive Dmentioning
confidence: 99%